Wood-boring limnoriids (Crustacea, Isopoda) including a new species from mangrove forests of the Tukang Besi Archipelago, Indonesia - Cookson, L. J.; Cragg, S. M.; Hendy, I. W. (Zootaxa, 2012)
In a survey of the fauna inhabiting fallen wood in Rhizophora-dominated forests of an archipelago of small islands to thesouth of Sulawesi, in Indonesia, four species of limnoriid (Limnoria insulae, L. pfefferi, L. sellifera new species and L.unicornis) were found feeding on the wood. L. sellifera is characterised by a saddle-shaped pleotelson that is smaller thanpleonite 5, transverse rows of teeth-like tubercles dorsomedially on pleonites 2–4 and a uropod with relatively small ex-opod, two rows of pointed tubercles on the peduncle, and one row on the endopod. L. sellifera is the second species ofLimnoria to be found exclusively on mangrove wood. The cephalon and pereon of the four species of limnoriids are anatomically similar, but they differ markedly in features of pleonite 5, the pleotelson and the uropods.